Husserlian Phenomenology of Professional Paradox in Military Physiotherapists - Ihat Mufliha; Susanne Dida; Saleha Rodiah (MIMBAR : Jurnal Sosial dan Pembangunan, 2026)
Military culture, emphasizing discipline, hierarchy, and obedience, often conflicts with healthcare practices centered on empathy and therapeutic communication, creating a professionalism paradox for military physiotherapists. This study explores how military physiotherapists interpret their profession and navigate therapeutic communication within hierarchical military structures. A Husserlian phenomenological approach was applied through in-depth interviews with eight Indonesian Army physiotherapists working in hospitals and military training centers in West Java. Findings reveal that physiotherapists continuously negotiate institutional demands, ethical responsibilities, and adaptive therapeutic communication in their professional experiences. Professionalism is understood not as a destructive conflict but as a reflective process for constructing ethical, communicative, and contextual professional identities. Therapeutic communication becomes central in building trust, ensuring patient safety, and balancing humanistic care with military structural demands. Strengthening institutional support, collaborative culture, therapeutic communication, and moral distress studies is essential for improving humanistic and professional military healthcare services.